Properties, Antioxidant and Antibacterial Activity of Southern Meagre Fish (Argyrosomus hololepidotus) Skin Gelatin Reinforced with Clove Bud Extract - Parvin Rostami; Ali Taheri; Mostafa Ghaffari (Gels)
The properties of biopolymer films prepared using Southern meagre fish (Argyrosomus hololepidotus) skin gelatin blends, both with and without clove bud extract (CE) at concentrations of 0.3% and 0.7%, were investigated. The addition of CE enhanced the light barrier properties and decreased water vapor permeability from 1.68 to 0.85 (×10−13 g s−1m−1Pa−1) (p < 0.05) in the films that contained CE. Additionally, the films’ water solubility diminished as the concentration of CE increased (89.20 to 69.04%) (p < 0.05). SEM images revealed a smooth, uniform surface without cracks in the samples both with and without CE, whereas the films that included CE displayed a rougher and denser cross-section. FTIR spectra revealed variations in peaks between the films containing CE and those without it. The incorporation of CE raised the glass transition temperature (51.04 to 58.80 °C) and the melting temperature (124.65 to 141.92 °C) of the films. Additionally, the antioxidant activities, assessed through DPPH free radical scavenging activity (86.97%) and reduction power (λ of 0.85), along with moderate antibacterial activities against four distinct foodborne pathogens, improved with increased concentrations of CE. It can be concluded that phenolic compounds, such as eugenol in the clove extract, facilitated the formation of additional bonds between the peptide helixes of the gelatin, thereby enhancing the properties of the CE-incorporated films. Thus, Southern meagre fish gelatin film containing CE is an effective active packaging biomaterial for seafood products, exhibiting satisfactory properties.